(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
Following the Uluru Statement from the Heart, historians are again tasked with ‘telling the truth’ about past human rights abuses in Australia. However, I argue that such a demand is too simplistic, and it is better to understand historians as producers of impermanent historical narratives which are embedded in public memory through the historian’s discursive authority and the authority of a supporting truth commission.